Peran Bahasa Arab Dalam Pembentukan Literasi Keagamaan dan Global Generasi Milenial dan Gen Z di Era Digital - Sintya (Suria Academic Press, 2025)
This artcle aims to examine indepth the role of Arabic in shaping the reading and understanding skills of religion, as well as the global competencies of millennials and Gen Z amidst an ancresingly complex and rapidly changing digital environment. This study uses a qualitative approach with library research methods, coleccting data from books, scientific articles, and report from international organizations that discuss learning Arabic, globalization, digitalization, and youth. The research result indicate that Arabic not only helps understand authentic Islamic teaching but is also an important tool for enhacing global insight, the ability to interact with other cultures, and the ability to compete internationally. Amidst the abudance of information circulating in the digital world, particularly on religious matters, Arabic language skilss enable young people to verify authentic sources and evaluate the veracity of their explanations. Furthermore, because Arabic is spoken by over 400 million people worldwide, it is vital asset in diplomacy, economics, technology, and international relations. Advances in digital technology also provide new opportunities for learning Arabic, such as through applications, online platforms, and artificial intelligence, which can be used flexibly and engagingly. Therefore, the restoration and development of Arabic is crucial in the modern education system to strengthen the religious and global competencies of millennials and Gen Z.